2017
DOI: 10.1016/j.ijhydene.2017.05.114
|View full text |Cite
|
Sign up to set email alerts
|

Application of Open Pore Cellular Foam for air breathing PEM fuel cell

Abstract: Open Pore Cellular Foam (OPCF) has received increased attention for use in Proton Exchange Membrane (PEM) fuel cells as a flow plate due to some advantages offered by the material, including better gas flow, lower pressure drop and low electrical resistance.In the present study, a novel design for an air-breathing PEM (ABPEM) fuel cell, which allows air convection from the surrounding atmosphere, using OPCF as a flow distributor has been developed. The developed fuel cell has been compared with one that uses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…The corrosion of flow plates, particularly when using metallic plates, is another reason for the degradation of PEMFC performance. Such corrosion increases the interfacial contact resistance and releases metal ions that can poison the catalyst, thus decreasing the proton conductivity of the membrane and reducing the power output [40,63,[200][201][202]. The degradation of the PEMFC is a complex phenomenon and severely limits the lifetime and the large-scale commercial applications.…”
Section: Merits and Challengesmentioning
confidence: 99%
“…The corrosion of flow plates, particularly when using metallic plates, is another reason for the degradation of PEMFC performance. Such corrosion increases the interfacial contact resistance and releases metal ions that can poison the catalyst, thus decreasing the proton conductivity of the membrane and reducing the power output [40,63,[200][201][202]. The degradation of the PEMFC is a complex phenomenon and severely limits the lifetime and the large-scale commercial applications.…”
Section: Merits and Challengesmentioning
confidence: 99%
“…The activation barrier is reduced by the catalyst but the voltage loss occursbecause of the slow reaction of oxygen. The total activation polarization over potential is 0.1 to 0.2 V. It reduces the maximum potential to less than 1.0 V.It increases with current density and can be expressed as: [10][11][12]…”
Section: Activation Polarization (Voltage Over Potential Loss)mentioning
confidence: 99%
“…They concluded that by increasing the Cu content in the Ni-P bath, the stainless-steel foam exhibited enhanced corrosion resistance, finer grain deposition and a lower deposit rate. Baroutaji et al [100]. investigated the surface coating of Nickel metal foam using Polytetrafluoroethylene (PTFE) coating techniques.…”
Section: Coating Of Open Porous Cellular Metal Foam Flow Channelmentioning
confidence: 99%